Anti-dengue Leads From Caesalpinia bonduc - An In Silico Approach (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Dengue (breakbone fever) is a rapidly spreading arboviral infection transmitted by Aedes mosquitoes with major public health implications in more than 100 tropical and subtropical countries mostly in Southeast Asia, South and Central America and the Western Pacific. As the virus spreads to new geographic areas, more frequent dengue outbreaks occur in different parts of the world. Fifty million cases of dengue occur worldwide each year, of which 10% require hospitalization for dengue hemorrhagic fever (DHF). It is a shocking truth that more than 90% of these are children under the age of five. The mortality rate is also significant as 2.5% die from dengue. Currently there is no effective vaccine or specific drug for Dengue/DHF. Pharmaceutical manufacturers have turned their attention to plant-based drug candidates to produce effective drugs. Following this the present study investigated the active phytochemicals present in the medicinal plant Caesalpinia bonduc (L.) Roxb. through docking simulation. Dengue virus non-structural protein five (NS5) and human IMPDH-II were used here as targets for docking with plant compounds. Docking results revealed that 33 compounds out of 82 phytochemicals showed better binding affinity than the native ligands of the targets. Compounds exhibiting the lowest free energy levels were further screened after studying their pharmacokinetics, medicinal chemistry friendliness, lead-likeness, and finally toxicity prediction to identify lead molecules. At the end of the study, three compounds, Caesaldekarin A, Caesalpinin F and Taepeenin D, which potently inhibited both targets, were selected here for further 'in vitro' and 'in vivo' studies.